2016
DOI: 10.1016/j.vaccine.2016.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability of school-located influenza vaccination programs in Florida

Abstract: Background School-located influenza vaccination (SLIV) programs are a promising strategy for increasing vaccination coverage among schoolchildren. However, questions of economic sustainability have dampened enthusiasm for this approach in the United States. We evaluated SLIV sustainability of a health department led, county-wide SLIV program in Alachua County, Florida. Based on Alachua’s outcome data, we modeled the sustainability of SLIV programs statewide using two different implementation costs and at diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Healthy school‐going children, although excluded from the defined vulnerable populations, are at a higher risk of contracting the influenza virus because of the increased probability of transmission due to more frequent close contact within this age group . School‐based influenza vaccination programs have therefore been recommended in some settings as an extension of existing influenza vaccination programs but remain rare globally . In Beijing, in 2009, a free influenza vaccination policy was launched in primary, secondary, and high schoolchildren who are 6‐18 years old .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Healthy school‐going children, although excluded from the defined vulnerable populations, are at a higher risk of contracting the influenza virus because of the increased probability of transmission due to more frequent close contact within this age group . School‐based influenza vaccination programs have therefore been recommended in some settings as an extension of existing influenza vaccination programs but remain rare globally . In Beijing, in 2009, a free influenza vaccination policy was launched in primary, secondary, and high schoolchildren who are 6‐18 years old .…”
Section: Introductionmentioning
confidence: 99%
“…rare globally. 3,4 In Beijing, in 2009, a free influenza vaccination policy was launched in primary, secondary, and high schoolchildren who are 6-18 years old. 5 Temporary points of vaccination (POVs) are established at schools, and students with their parent's written consent are organized to receive the vaccination there.…”
mentioning
confidence: 99%
“…Citing the randomized trial (11), the Advisory Committee on Immunization Practices began recommending influenza vaccination for children (13). Since then, local public health agencies initiated school-located programs, demonstrated to be epidemiologically effective and economically sustainable (14)(15)(16). These implementations highlight the translation of modeling analyses to improve preventative health.…”
Section: Discussionmentioning
confidence: 99%
“…Health provider recommendation, email reminders from health maintenance organizations, workplace incentivization, and optout scheduling of vaccination appointments are also influential in promoting vaccination (22)(23)(24)(25). These efforts can be augmented by improving the accessibility of vaccination; for instance, through active recruitment at convenient locations such as pharmacies, retail establishments, community centers, workplaces, and schools (14,16,25,26). When herd immunity is anticipated to be inadequate to protect the elderly, our results highlight the importance of making an extra effort to encourage vaccination uptake in this age class.…”
Section: Discussionmentioning
confidence: 99%
“…68 Another program in Florida similarly found that school-located influenza vaccination programs can be economically sustainable by targeting adequate numbers of privately insured children and reducing costs through volunteers and mass vaccination. 69 • School nurses School nurses who are part of a school health program that is enrolled as a Vaccines ForChildren program provider play an integral role in achieving and maintaining high coverage of adolescent immunizations. 70 They can be valuable resources for delivering vaccines because of their knowledge of the school and its students, and access to immunization information systems may help increase their ability to provide vaccines to adolescent students.…”
Section: The School As An Alternative Vaccination Sitementioning
confidence: 99%